A Study of the Perceived Life Significance of a University Outdoor Education Course - Wigglesworth, Jennifer (Université d'Ottawa / University of Ottawa, 2012)
Relatively little research exists on the life significance of outdoor education (OE) programs and courses. There is increasing interest in the OE field to move beyond simply focusing on program-specific outcomes to developing more evidence-based models that analyze the influence of specific mechanisms of change. The purpose of the present study was to investigate the significant life effect of a university OE course upon participants after the course, including the effect of the course upon participants’ intrapersonal, interpersonal and environmental relationships. The present investigation was a two part qualitative-quantitative study. The overarching research question was: What is the perceived life significance of a university undergraduate OE course? The current study involved in-depth interviews with a purposive intensity sample of 17 University of Ottawa alumni who had taken one of the university’s OE courses more than 20 years ago, followed by a web-based survey questionnaire completed by 46 University of Ottawa alumni and students who had taken one of the university’s OE courses between 1975 and 2009. Some of the survey participants had taken both the summer and winter OE courses offered by the University of Ottawa so there was a total of 65 separate course responses in the quantitative study. The findings from this study suggested that the OE course led to development of interpersonal skills, self-discovery, environmental impacts, leisure style change, and increased outdoor knowledge and skills amongst the participants. The idea that this outdoor knowledge and skills was transferred to others (e.g., students and children) also emerged from the data. In addition, in some instances participants expressed the idea that the OE course helped confirm or reinforce already-held beliefs about the outdoors. It is hopeful that the current findings can contribute to OE professional practice and demonstrate the need for OE in university settings.
Keywords: Outdoor education; Significant life experience